PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN (STUDI PADA PELANGGAN KFC CABANG BATURAJA) - Sri - Rahayu; Maulana Hadi Kusuma (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
This study aimed to determine the effect of Brand Image on Customer Satisfaction, determine the effect of Product Quality on Customer Satisfaction, determine the effect of Customer Satisfaction on Customer Loyalty, determine the effect of Brand Image on Customer Loyalty, determine the effect of Product Quality on Customer Loyalty. The type of research used is explanatory research with quantitative approach. The research conducted by Purposive techniques of 100 customer of KFC Branch Baturaja. Data were collected through questionare. Descriptive analysis and path analysis were used as data analysis techniques.The result of the study reveals that Brand Image has direct and significant effect on Customer Satisfaction, Product Quality has direct and significant effect on Customer Satisfaction, Customer Satisfaction has direct and significant effect on Customer Loyalty, Brand Image has direct and not significant effect on Customer Loyalty, Product Quality has direct and significant effect on Customer Loyalty. Thus, the company should continue to improve the brand image and product quality of KFC Branch Baturaja, so that customer will continue to become a loyal customer. KFC Branch Baturaja should continue to deliver satisfaction to its customer.